2013
DOI: 10.1016/j.bone.2013.01.043
|View full text |Cite
|
Sign up to set email alerts
|

Reduced gravitational loading does not account for the skeletal effect of botulinum toxin-induced muscle inhibition suggesting a direct effect of muscle on bone

Abstract: Intramuscular injection of botulinum toxin (botox) into rodent hindlimbs has developed as a useful model for exploring muscle-bone interactions. Botox-induced muscle inhibition rapidly induces muscle atrophy and subsequent bone loss, with the latter hypothesized to result from reduced muscular loading of the skeleton. However, botox-induced muscle inhibition also reduces gravitational loading (as evident by reduced ground reaction forces during gait) which may account for its negative skeletal effects. The aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 36 publications
4
31
1
Order By: Relevance
“…In a study conducted with forty virgin female mice up to 14 weeks of age which of each animal was injected with Botox in the right posterior leg and with vehicle in the left posterior leg, after muscle inactivation, animals were randomly separated into two groups: 1) cage control and 2) tail suspended for six weeks and it was found that the skeletal effects of Botox-provoked muscle inactivation are not only due to the diminution of gravitational forces 20 . The retraction of gravitational forces of the posterior legs through tail suspension caused a loss of bone mass as a result of declined periosteal bone formation and increased endosteal bone resorption 20 .…”
Section: Muscle Loads and Bone Tissue: Results From Genetic Mice Modementioning
confidence: 99%
See 3 more Smart Citations
“…In a study conducted with forty virgin female mice up to 14 weeks of age which of each animal was injected with Botox in the right posterior leg and with vehicle in the left posterior leg, after muscle inactivation, animals were randomly separated into two groups: 1) cage control and 2) tail suspended for six weeks and it was found that the skeletal effects of Botox-provoked muscle inactivation are not only due to the diminution of gravitational forces 20 . The retraction of gravitational forces of the posterior legs through tail suspension caused a loss of bone mass as a result of declined periosteal bone formation and increased endosteal bone resorption 20 .…”
Section: Muscle Loads and Bone Tissue: Results From Genetic Mice Modementioning
confidence: 99%
“…The retraction of gravitational forces of the posterior legs through tail suspension caused a loss of bone mass as a result of declined periosteal bone formation and increased endosteal bone resorption 20 . The increase in endosteal bone resorption was noticeable by a significant increase in medullary area and a decline in cortical area and cortical thickness 20 .…”
Section: Muscle Loads and Bone Tissue: Results From Genetic Mice Modementioning
confidence: 99%
See 2 more Smart Citations
“…BOTOX®), which is an extremely powerful agent to block neuromuscular transmission. They found decreases in bone strength and mass in mice 23 . Basically the studies suggested that BOTOX® had a deleterious effect in animal bones' especially trabecular bone 24 .…”
Section: Muscle-bone Interactionsmentioning
confidence: 99%